THE IMPORTANCE OF INFORMED CONSENT IN LABOR AND DELIVERY CARE - Vittes, Adriana (2024)
This letter to the editor addresses the importance of informed consent in obstetric care in Peru. It highlights that, despite being legislated, many women do not receive adequate information for effective informed consent in practice, especially during labor. This omission affects the physical and emotional health of mothers and neonates and undermines trust in the healthcare system. Factors such as lack of training among medical staff, cultural and linguistic barriers, paternalistic practices, and the misconception of labor as an emergency contribute to this situation. To improve it, measures such as training healthcare personnel in informed consent, empowering women in their childbirth process, implementing clear policies and protocols in healthcare institutions, and strengthening monitoring and supervision are proposed. This will not only enhance the childbirth experience but also improve equity in medical care and promote human rights in Peru.